Algunos factores determinantes de la cosmética dental (2003)
ABSTRACT: Several factors influence dental cosmetics. Among them are: individual dental proportions, relationship between lips and dental structures (contact, absence of contact, or coverage), different types of smiles (high, medium or low) and number of teeth exposed in smiling, etc. This is a descriptive-correlational study with a sample of 87 students (male and female in different proportions) 18 to 30 years of age from the Universidad de Antioquia, School of Dentistry. The "golden" proportions were not met in the majority of the subjects studied in the sample, either vertically nor horizontally. The parallelism relationship and the absence of contact between the upper incisal edge and the lower lip were the most frequently found; the former 74.71% and the latter 67.81%. Regarding the types of smile. high, medium and low; the medium smile was most frequent (58.62%). The highest number of teeth exposed in smiling is 10 (49.42%), followed by the exposure of 12 or more teeth (40.22%). The most frequent clinical parameters can be considered as a guide to establish a typical or average smile and should not be interpreted as rigid cosmetic rules. Key words: Dental cosmetic, Proportions, Smile.